PENGARUH BEBAN PAJAK TANGGUHAN, ASET PAJAK TANGGUHAN DAN PERENCANAAN PAJAK TERHADAP MANAJEMEN LABA PADA INDUSTRI MAKANAN DAN MINUMAN - Hilal Hamdi; Utami, Tri (Jurnal Nusa Akuntansi, 2024)
This study aims to analyze and obtain empirical evidence regarding the influence of deferred tax expenses, deferred tax assets, and tax planning on earnings management in the food and beverage sector companies listed on the Indonesia Stock Exchange for the period 2018 – 2022. This research is a quantitative study with an associative method, and the data used in this study are secondary data. The data analysis method used is panel data regression, processed using Eviews version 12. The population used in this study consists of energy sector companies listed on the Indonesia Stock Exchange for the period 2018 – 2022, totaling 84 companies. The sample selection in this study uses purposive sampling techniques. The obtained sample consists of 16 companies with a research period of 5 years, resulting in a total of 80 data points. The results of this study indicate that, partially, deferred tax assets do not have a significant effect on earnings management, but deferred tax expenses and tax planning have a significant effect on earnings management. Deferred tax expenses, deferred tax assets, and tax planning simultaneously have a significant effect on earnings management.